2006
DOI: 10.1007/s10750-006-0306-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophysical processes in Lake Baikal in its transition from subtropical to modern climates

Abstract: During the past 5 million years significant changes have taken place in the Lake Baikal ecosystem. The climate changed from subtropical, with average annual air temperatures (T air ) of 15-10°C, to a moderate one with T air of $0°C. The modern hydrophysical regime of the lake has been formed with increase in depth, and gradual cooling of the water body from deepwater temperatures (T dw ) of 15-10°C to below 4°C. The processes of cooling of Lake Baikal water in its transition from subtropical climate with deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…, Macdonald et al. , Yokoyama and Goto , Sherstyankin and Kuimova , Schön and Martens , Karanovic and Sitnikova ), while algae have largely been ignored in evolutionary studies, with the exception of diatoms (Mann , Flower , Edlund and Soninkhishig , Kulikovskiy et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, Macdonald et al. , Yokoyama and Goto , Sherstyankin and Kuimova , Schön and Martens , Karanovic and Sitnikova ), while algae have largely been ignored in evolutionary studies, with the exception of diatoms (Mann , Flower , Edlund and Soninkhishig , Kulikovskiy et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…, Karanovic and Sitnikova ). During the last 5 My, the lake passed through several climate changes, from a subtropical (~5 Mya), a transitional stage (from ~2.6 to 2.4 Mya), to the current cold‐temperate climate (Sherstyankin and Kuimova ). Although the origin of the species and the timing of their radiation has not been investigated in all groups, it has been suggested that the cooling of the lake during the Pleistocene (~2 Mya) produced many of the species assemblages that are present to date (Sherbakov , Mats et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Geological and climatic reconstructions provide further detailed information on the time of origin of these lakes and on changing environmental conditions over the millions of years of their history (e.g. for Lake Baikal (LB): Karabanov et al, 2004;Sherstyankin & Kuimova, 2006, for LT: Cohen et al, 1993, 1997Lezzar et al, 1996;Nicholson, 1999;Scholz et al, 2003). Molecular research on evolution and speciation of ancient lake taxa has mainly focused on cichlid fish (see Seehausen, 2006, andKoblmüller et al, 2008, for more recent reviews on cichlids), although molecular analyses on invertebrates such as crabs (Marijnissen et al, 2006(Marijnissen et al, , 2008, snails (West & Michel, 2000;Wilson et al, 2004;Albrecht et al, 2006Albrecht et al, , 2008Hauswald et al, 2008;Schultheiß et al, 2008), sponges (Schröder et al, 2002) and amphipods (Macdonald et al, 2005) have meanwhile also been published.…”
Section: Introductionmentioning
confidence: 99%